Manajemen Sarana dan Prasarana Pendidikan Dalam Perspektif Islam - Abdulah Jawawi (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2019)
Management of facilities and infrastructure in Islamic perspective. Education includes administering and managing well education Management is the foundation of Islam Qur'an and Hadith with the principle of Tauhid, Khalifah and trustful. Furthermore, the function of which is popularly called management Planning, Organizing, Actuating and Controlling, in line with the teachings of the Qur'an, that in life and life, man must have the planning , organization , unity and mutual cooperation. In addition it should also be able to move others to do good in the form of motivation, advice and guidance . Then needs to be controlled and monitored in order to get maximum results.